2006
DOI: 10.2214/ajr.05.0930
|View full text |Cite
|
Sign up to set email alerts
|

Iterative Decomposition of Water and Fat with Echo Asymmetry and Least-Squares Estimation (IDEAL) Fast Spin-Echo Imaging of the Ankle: Initial Clinical Experience

Abstract: IDEAL fast spin-echo imaging is a promising technique for MRI of the ankle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 14 publications
0
34
0
1
Order By: Relevance
“…Several studies have reported on the usefulness of the IDEAL technique with respect to improving image quality by reducing artifacts in the extremities and spine (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). Previous reports have mentioned that the IDEAL technique improves visibility of the detailed anatomy (4)(5)(6)(7)(8)(9)(10)(11)(12), by enabling more homogeneous fat suppression and reducing tissue obscuring artifacts produced around metallic fixation devices in the spine.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have reported on the usefulness of the IDEAL technique with respect to improving image quality by reducing artifacts in the extremities and spine (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). Previous reports have mentioned that the IDEAL technique improves visibility of the detailed anatomy (4)(5)(6)(7)(8)(9)(10)(11)(12), by enabling more homogeneous fat suppression and reducing tissue obscuring artifacts produced around metallic fixation devices in the spine.…”
Section: Discussionmentioning
confidence: 99%
“…1, 2). Several studies have reported on the effectiveness of IDEAL for reducing the degrees of susceptibility artifacts around areas exhibiting abrupt contour changes in the extremities (12)(13)(14). Metallic artifacts around metallic implants cause failed fat suppression and signal loss due to inadvertent water suppression caused by magnetic field inhomogeneity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Las secuencias convencionales fast spin echo en ponderación T1, T2 y STIR fueron reemplazadas por secuencias 3 D de alta resolución que derivan del método Dixon (13) , que trabaja en base a imágenes en fase/fuera de fase, con saturación de agua y/o de grasa. La secuencia IDEAL (Iterative Decomposition of water and fat with Echo Asymmetry and Least-squares estimation-GE Healthcare, USA), permite el empleo de imágenes en ponderación T1 y T2 con cuatro combinaciones de pulsos de saturación: supresión de agua, supresión de grasa y supresión combinada de agua y grasa en fase y fuera de fase (14,15) . En nuestro protocolo de estudio, ante la presencia de lesiones de aspecto tumoral/pseudotumoral se añaden secuencias de difusión (DWI) y tensor de difusión (DTI) (16,17) .…”
Section: Consideraciones Técnicasunclassified
“…The Iterative Decomposition of Water and Fat with Echo Asymmetry and Least-Squares Estimation (IDEAL) FSE imaging has been shown to be a promising fat-suppression technique compared with conventional fat-suppressed FSE MRI of the ankle with excellent SNR and image quality. 12 Potential advantages compared with standard frequency-specific fat-suppression FSE include superior fat-water separation, improved diagnostic quality, superior fluid-cartilage contrast-to-noise ratio, and less image degradation caused by metallic hardware. Disadvantages include slightly longer imaging time and lack of a no-phase-wrap option.…”
Section: T Mri Technique and Artifactsmentioning
confidence: 99%